Impact of psychiatric comorbidity on the severity, short-term functional outcome, and psychiatric complications after acute stroke - Hoyer, Carolin; Schmidt, Hanna; Kranaster, Laura; Alonso, Angelika (Neuropsychiatric disease and treatment, 2019)
Background and purpose: The comorbidity of psychiatric disorders and cerebrovascular disease appears to be complex with underlying bidirectional influences. Hitherto, research has focused mainly on the evaluation of stroke risk in particular psychiatric disorders; only a few studies have assessed their role in the acute natural history of stroke. The aim of this study was to provide a perspective on psychiatric premorbidity and its impact on stroke severity, psychiatric complications during the initial treatment phase, and the short-term functional outcome of stroke. Patients and methods: We retrospectively studied the impact of a predocumented psychiatric diagnosis (PDPD) on stroke severity, short-term functional outcome, and psychiatric complications in a sample of 798 patients consecutively admitted for acute ischemic or hemorrhagic stroke by performing a chart review. Group comparisons (PDPD vs non-PDPD) with adjustment for covariates were carried out either using multivariate analysis of variance or logistic regression analysis. Results: More severe strokes (ie, mean National Institute of Health Stroke Scale score on admission 10.1 +/- 7.9 vs 7.5 +/- 7.4; F(10,796)=18.5, p<0.0001) and higher prevalence of poor outcome (73.7 vs 54.9%; OR: 2.6, standard error: 0.5, z=4.82, p<0.0001) was found in patients with a documented psychiatric diagnosis at the time of stroke, as well as a higher rate of psychiatric complications during the initial treatment phase (46.7 vs 28.9%; OR: -0.78, z=4.59, p<0.0001). Conclusion: Our data have clinical implications in that they call for identification of psychiatric premorbidity or comorbidity through careful history-taking and particularly close monitoring for psychiatric complications with respect to their potentially negative impact on outcome after stroke.